2015
DOI: 10.1016/j.frl.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Stock return predictability in South Africa: The role of major developed markets

Abstract: We examine stock return predictability of the South African (SA) market using lagged country monthly returns of the US, the UK, Germany, and Japan during the period from January 1973 to December 2014. Our results show that SA market return and industry returns can be significantly predicted by lagged US market return and industry returns, mainly in the pre-1996 market change period. Lagged German and Japanese returns have no predictive ability, while lagged UK returns only provide some degree of predictive pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Aye et al (2013) found evidence of structural instability and variability in the predictive ability of the twenty-three variables in different regimes. Wen et al (2015) found that US and UK market return could predict South African stock returns pre-1996 than post-1996, possibly due to regulatory reforms in the latter period. Smith and Dyakova (2014), analysing the return predictability on eight stock markets including South Africa, found that there were successive periods of predictability and non-predictability, a finding which is consistent with the Adaptive Market Hypothesis of Lo (2004).…”
Section: Macroeconomic Variables and Predictability Of Returns On The South African Marketmentioning
confidence: 95%
See 1 more Smart Citation
“…Aye et al (2013) found evidence of structural instability and variability in the predictive ability of the twenty-three variables in different regimes. Wen et al (2015) found that US and UK market return could predict South African stock returns pre-1996 than post-1996, possibly due to regulatory reforms in the latter period. Smith and Dyakova (2014), analysing the return predictability on eight stock markets including South Africa, found that there were successive periods of predictability and non-predictability, a finding which is consistent with the Adaptive Market Hypothesis of Lo (2004).…”
Section: Macroeconomic Variables and Predictability Of Returns On The South African Marketmentioning
confidence: 95%
“…Monthly closing prices, dividend and earnings yields for seven sector indices namely, Basic Materials (J510), Industrials (J520), Consumer Goods (J530), Health Care (J540), Consumer Services (J550), Telecommunication (J560) and Financials (J580), and the All-Share Index (J203), were obtained from the IRESS database from 1996:01 to 2018:12. This was necessitated by data availability and the beginning of this period coincides with the period in which major economic and regulatory reforms were instituted in South Africa (Wen et al, 2015). The nominal components were deflated by the consumer price index obtained from the South African Reserve Bank.…”
Section: Data and Samplementioning
confidence: 99%
“…Wen et al ( 2015 ) also studied international markets and demonstrated that US stock returns could predict South African returns from 1973 to 2014. Cambón and Vaduva ( 2017 ) showed that Spanish industries, which provided valuable and important economic information, drove neither equity markets nor economic activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a few studies, such as Arshanapalli and Doukas ( 1993 ), Beine et al ( 2010 ), Junior et al ( 2021 ), and Liu et al ( 2017 ) use daily international data, some of them recognize the non-synchronous trading problem arising from different time zones (for instance, Tokyo and Shanghai are 14 and 12 h ahead of New York, respectively). Most studies that consider the US and Asia–Pacific countries use monthly data (e.g., Asafo-Adjei et al 2021 ; Nyberg and Pönkä 2016 ; Rapach et al 2013 , 2015 , 2019 ; Roll 1992 ; Tse 2018 ; Wen et al 2015 ). The lead-lag effects tend to increase with data frequency; hence, if daily data is synchronous, it will present larger auto- and cross-correlations because there is better information to compensate for the rapid fluctuations of financial information.…”
Section: Data Description and Preliminary Analysismentioning
confidence: 99%
“…In financial economics among the various financial assets, the body of work exploring aspects of stock returns predictability is voluminous (e.g., Boucher, 2007; Campbell & Hamao, 1992; Dergiades, Milas, & Panagiotidis, 2020; Henkel, Martin, & Nadari, 2011; Wen, Lin, Li, & Roca, 2015). The prevailing view is that stock return variation is predictable, but principally at long horizons.…”
Section: Introductionmentioning
confidence: 99%